Relationship between digital parental awareness with health literacy and a variety of variables among mothers - Pazarcıkcı, Fahriye; Ağralı, Hatice; Aydınlı, Ayşe (Journal of Dependence, 2022)
Objective: This study aimed to reveal the relationship between digital parenting awareness with health literacy and a variety of variables among mothers. Method: The study is a quantitative research in correlational design. The sample for the research comprised 311 mothers with children aged 5-11 years. Data for implementation and assessment in the research used the personal information form, digital parenting awareness scale and health literacy scale. The research data were obtained through an online survey. Results: The mean age of the mothers is 30.23±4.85. 62.1% of the mothers are living in the city center for the last six months. Children of 7.1% of mothers have a smart phone, while children of 39.2% have a tablet PC. 48.2% of the mothers spent enough time with their children. It is found that mothers have high digital parenting awareness and health literacy level. As the health literacy levels of the mothers decreased, the levels of being a negative model, digital neglect increased at significant level. Also, if the level of health literacy increases, the levels of efficient use, protection from risks also increase. Farther that children have smartphones/tablet computers and mothers spend enough time with their children, it also affects the digital parenting awareness of the region where they live for the last six months. Conclusion: It is recommended to organize programs that improve mothers’ health literacy and digital parenting roles, and increase quality of their digital environment. It is anticipated that these programs will contribute to protection of public health.